Detection of Salmonella on Fried Rice Served in Restaurant of Economic Class Train - . Srianta; Elisa Rinihapsari (Jurnal Teknologi dan Industri Pangan, 2003)
Salmonella is a group of infective pathogenic bacteria for human being that cause many food borne disease outbreaks. Human, animal and some animal-based food products are whicle for Salmonella. Public transportation i.e. train/railway, often serve foods that potentially contaminated with Salmonella. Study on Salmonella detection on fried rice served in economic class train restaurant is necessary for controlling its safety and quality. Standard method was used to detect Salmonella on fried rice including isolation on 2 (two) different selective media, i.e. Bismuth Sulphite Agar and Salmonella-Shigella Agar media (macroscopic and microscopic study) and Biochemical test i.e. sugar and IMVIC test. This study showed that twenty three (23) colonies which, have been found of 8 (eight) samples of fried rice were identified as Salmonella. It indicated that the fried rice was not well processed. The train restaurant has to improve the fried rice prepared and sanitation to obtain a safe food product and to prevent the spreading of this bacteria. Key words: Salmonella, Salmonella detection, fried rice, train, restaurant